Exosome encapsulation of miR-205-5p suppresses neuroblastoma progression by targeting RUNX2 - Qi Liu; Jiaxiang Tang; Binyi Yang; Hongting Lu (World Journal of Pediatric Surgery, 2025)
Objective This study investigates the tumor-suppressive role of microRNA (miR)-205-5p in neuroblastoma (NB) and evaluates exosome-mediated delivery of miR-205-5p as a therapeutic strategy.Methods miR-205-5p expression in NB cells was quantified via quantitative reverse transcription PCR. Functional assays (CCK-8, colony formation, wound healing, Transwell) assessed proliferation, migration, and invasion. Bioinformatic tools and dual-luciferase assays identified miR-205-5p/Runt-related transcription factor 2 (RUNX2) binding. RUNX2 rescue experiments reversed miR-205-5p effects. Exosomes from SH-SY5Y cells transfected with miR-205-5p mimics/NC (negative control) lentiviruses were isolated, characterized, and co-cultured with recipient cells. In vivo, subcutaneous NB xenografts in nude mice were established using OE-miR-205-5p, sh-miR-205-5p, or NC lentiviral cells, followed by exosome injections to evaluate tumor growth.Results miR-205-5p was downregulated in NB cells. Its overexpression suppressed proliferation, migration, invasion, and tumor growth in vitro and in vivo. RUNX2 was confirmed as a direct target; its restoration reversed miR-205-5p-mediated inhibition. Exosomes efficiently delivered miR-205-5p to recipient cells, downregulating RUNX2 and impairing malignant behaviors. In mice, miR-205-5p-enriched exosomes significantly inhibited tumor progression.Conclusions Exosome-encapsulated miR-205-5p inhibits NB progression by targeting RUNX2, highlighting its potential as a novel therapeutic modality.